Penerapan Social Skills Training (SST) untuk Meningkatkan Social Skill Performance pada Anak - Qamaria, Rezki Suci (Happiness: Journal of Psychology and Islamic Science, 2023)
As social beings, everyone is required to be able to adjust in the social environment. But in fact, there are individuals who have difficulty adjusting because they have social skills deficits. Deficits of social skills can be measured using the social skills rating system (SSRS) which refers to the theory of Gresham and Elliott which explains that there are three aspects that can be used as a reference for measuring social skills, namely the ability to cooperate, assertive behavior, and the ability to control oneself. Based on these conditions, researchers conducted experimental research to determine the effectiveness of Social Skills Training (SST) as an effort to overcome social skill deficits owned by individuals. This study involved a 7-year-old boy who was studying at an elementary school. Based on the results of the SSRS measurement, the child has a deficit in social skills. The method used in this research is a single case experimental design (DEKT), with pre-test and post-test applied to the subject. The result is Social Skills. The training was able to improve the subject's social skills. The increase that occurred included all three aspects of social skills, namely the subject had shown the ability to work together with his peers, was able to convey what he wanted, thought, and felt, and was able to control himself when he was in an unpleasant situation. Overall, the subject's social skills after the SST intervention were in the high category.